Estimation of Ozone and Nitrogen Dioxide Pollutants in Mazandaran Province Using Sentinel 5 Satellite Images - A. Yousefi Kebriya; M. Nadi; E. Ghanbari Parmehr (Iranica Journal of Energy and Environment, 2025)
Mazandaran province, due to its strategic geographical location and high influx of tourists during holidays, coupled with the presence of power plants and industrial complexes, is facing pollution challenges. This research, conducted in 2022, focuses on monitoring nitrogen dioxide and ozone pollutants in the province and investigating the role of tourists during certain multi-day holidays. Utilizing Sentinel 5 satellite imagery, including daily images from holidays and non-holidays, the study compensates for the lack of regular pollution data in Mazandaran's monitoring stations by validating the satellite data against Tehran stations. Linear regression equations determine the levels of nitrogen dioxide and ozone pollutants, leading to the creation of an Air Quality Index (AQI) map for Mazandaran province during holidays. The results highlight a strong correlation (0.3-0.7) between satellite and ground data, with ozone pollutants exhibiting a higher correlation. The skew error is consistently zero, and the mean square error varies between 1.9-6.2 ppb for nitrogen dioxide and 1.1-5.1 ppb for ozone. Pollution estimates for different points in Mazandaran province during holidays and non-holidays indicate higher ozone pollution compared to nitrogen dioxide. Ozone pollution is particularly unhealthy and very unhealthy during holiday periods, especially along the coastal areas, while non-holiday days show cleaner and healthier air quality. The pollution index map illustrates higher ozone pollution in coastal cities during holidays compared to other regions, emphasizing the impact of tourists. This research demonstrates the effectiveness of Sentinel 5 satellite in monitoring air pollution and underscores the significant influence of tourists and transportation on Mazandaran province's air quality. The findings advocate for sustainable tourism practices to mitigate the adverse effects on Mazandaran's air quality during holidays.